Perkawinan Bawah Umur dan Potensi Perceraian (Studi Kewenangan KUA Wilayah Kota Bogor) - Ani Yumarni; Endeh Suhartini (Fakultas Hukum Universitas Islam Indonesia, 2019)
This study examines: first the authority of VAT on Religion Affair Office (KUA) in Sub district of Bogor City Region in creating an orderly administration of registering the underage marriages, and secondly the assessment of the relevance of underage marriage with the high divorce rates in Bogor City Region.This is an empirical juridical research. From the results of this research, it can be concluded that, first, the VAT Institution in Bogor City has made some maximum efforts to create the orderly marital administration as mandated by law. It is also reaffirmed by the Circular of the Ministry of Religion of RI regarding the implementation of the Marriage Administration System (SIMKAH), which increasingly narrows the space for people to do an underage marriage. Second, the prevalence of underage marriage has the relevance to the high divorce rate also dominated by couples aged 21-30 years. It is because even if the marriage is 'not registered', due to being underage according to the law, it still has an opportunity to obtain legality through legal action to submit a marriage permit application in the Religious Court. In addition, emotional immaturity and household unpreparedness are the factors of high divorce among young couples undergoing an underage marriage.